2013
DOI: 10.1073/pnas.1221835110
|View full text |Cite
|
Sign up to set email alerts
|

Severing and end-to-end annealing of neurofilaments in neurons

Abstract: We have shown previously that neurofilaments and vimentin filaments expressed in nonneuronal cell lines can lengthen by joining ends in a process known as "end-to-end annealing." To test if this also occurs for neurofilaments in neurons, we transfected cultured rat cortical neurons with fluorescent neurofilament fusion proteins and then used photoconversion or photoactivation strategies to create distinct populations of red and green fluorescent filaments. Within several hours we observed the appearance of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 57 publications
6
49
0
Order By: Relevance
“…This reorganization consists of active transport of filaments and filament precursors and also the assembly and disassembly of filaments. Photoconversion approaches were used to demonstrate that although vimentin filaments are rapidly transported along microtubules, the most dominant form of mature filament dynamics occurs by slow severing and reannealing (15,16). These experiments are consistent with in vitro data demonstrating that vimentin filaments elongate by end-to-end annealing of ULFs and short filaments (7).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This reorganization consists of active transport of filaments and filament precursors and also the assembly and disassembly of filaments. Photoconversion approaches were used to demonstrate that although vimentin filaments are rapidly transported along microtubules, the most dominant form of mature filament dynamics occurs by slow severing and reannealing (15,16). These experiments are consistent with in vitro data demonstrating that vimentin filaments elongate by end-to-end annealing of ULFs and short filaments (7).…”
Section: Discussionsupporting
confidence: 66%
“…However, live-cell imaging demonstrates that IF networks are in fact quite dynamic and undergo rapid rearrangement in cells (12,15,16,(28)(29)(30)(31). This reorganization consists of active transport of filaments and filament precursors and also the assembly and disassembly of filaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of intermediate filament assembly in cells is not well understood, but it is likely that the mechanism of fusion protein incorporation into neurofilaments involves de novo filament assembly, subunit exchange along the length of pre-existing filaments (which we have termed intercalary subunit exchange (Colakoglu and Brown, 2009)), and also cyclical annealing and severing mechanisms (Uchida et al, 2013). Regardless of the imaging strategy to be used, it is preferable to allow time for expression and incorporation of the fluorescent fusion protein throughout the axonal neurofilament array before imaging.…”
Section: Live-cell Imagingmentioning
confidence: 99%
“…Using immunostaining to compare the distribution of the fusion protein to endogenous neurofilament proteins, we have found that this takes a minimum of several days. For SCG neurons transfected by nuclear injection 2 days after plating, we usually image 3–5 days later (Wang and Brown, 2001; Wang et al, 2000), whereas for cortical neurons transfected by electroporation we usually image 7–14 days later (Wang et al, 2010; Uchida et al, 2013). With enough time, the fusion protein should incorporate along the entire length of all neurofilaments throughout the axonal neurofilament array.…”
Section: Live-cell Imagingmentioning
confidence: 99%